(untitled) (Revista Tempo e Argumento, 2019)
Abstract ‘Exact’ anniversary dates of the 1964 coup—those marking the passage of each decade—have served as moments of spirited public and academic debate about the military dictatorship. This article discusses some of these controversies, particularly concerning the following themes: the nature of the coup, the nature of the regime, the relationship between civil society and the dictatorship, the role of the armed struggle, and the periodization of the dictatorship. The purpose is to historically situate the emergence and development of each of these debates, in addition to discussing their political repercussions. The article analyzes the longevity and endurance of some of these debates, as well as the growth of academic and public interest in the military dictatorship and its legacies. Keywords: Dictatorship. 1964 Coup. Historiography. History of the Present Time. Commemorative Dates.